1985
DOI: 10.1111/j.1365-3032.1985.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

The selection for early and late pupariation in the flesh‐fly, Sarcophaga argyrostoma, and its effect on the incidence of pupal diapause

Abstract: Artificial selection from the first and last larvae of Sarcophaga argyrostoma (Robineau-Desvoidy) to form puparia gives rise to two strains, 'fast' (F) and 'slow' ( S ) , 'fast' pupariating about 3 days earlier than 'slow' in continuous light, 25°C. The two strains differ only in the time from larval wandering to pupariation; other aspects of development are identical. In light-dark cycles (17°C) the distributions of pupariation times in 'fast' are unimodal and nearly normal, whereas those for 'slow' are multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…similis shows a clear photoperiodic response not only in the pupal stage (diapause) but also in the larval stage, i.e., larvae reared under short-day conditions pupariated later than those reared under long-day conditions (see also Goto, 2009). Such photoperiodic responses in the larval period were also reported in several other flesh fly species (Henrich and Denlinger, 1982;Bradley and Saunders, 1986;Moribayashi et al, 1988Moribayashi et al, , 2008. Interestingly, when diapause-destined larvae of S. similis were exposed to 3 cycles of long days, some larvae altered their developmental program from diapause to nondiapause and pupariated significantly earlier than individuals destined for diapause.…”
Section: Discussionsupporting
confidence: 64%
“…similis shows a clear photoperiodic response not only in the pupal stage (diapause) but also in the larval stage, i.e., larvae reared under short-day conditions pupariated later than those reared under long-day conditions (see also Goto, 2009). Such photoperiodic responses in the larval period were also reported in several other flesh fly species (Henrich and Denlinger, 1982;Bradley and Saunders, 1986;Moribayashi et al, 1988Moribayashi et al, , 2008. Interestingly, when diapause-destined larvae of S. similis were exposed to 3 cycles of long days, some larvae altered their developmental program from diapause to nondiapause and pupariated significantly earlier than individuals destined for diapause.…”
Section: Discussionsupporting
confidence: 64%
“…They also show a clear photoperiodic response in the larval period (i.e. larvae reared under shortday conditions pupariate later when compared with those reared under long-day conditions; Henrich & Denlinger, 1982;Bradley & Saunders, 1986;Moribayashi et al , 1988Moribayashi et al , , 2008. Thus, the flesh fly shows photoperiodic responses in the larval stage as well as in the pupal stage; however, the genetic relationship between these responses at different stages is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting for pupation time of Tribolium castaneum, Englert and Bell (1970) suggested that phenotypic differences in pupation time could reflect variation in hormonal activity manifested in growth and development. Bradley and Saunders (1986) found that in the flesh fly, Sarcophaga argyrostoma, the 'fast' and 'slow' selection only differed in the interval of larval wandering to pupariation, other aspects of development being identical. They held the view that 'fast' or 'slow' selection operated on genes regulating aspects of the release prothoracicotropic hormone (PTTH).…”
Section: Discussionmentioning
confidence: 94%